Adenovirus Methods and Protocols - Chillón, Miguel; Bosch, Assumpció; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2014)
Reflecting the development of powerful new tools and high-throughput methods to analyze adenoviral particles and their interactions with host cells, the third edition of Adenovirus Methods and Protocols calls upon experts in the field to convey advances in molecular biology, genomics and proteomics, imaging, and bioinformatics.  Beginning with cryo-electron microscopy, atomic force microscopy, and mass spectrometry for a high resolution image and characterization of the virion, this detailed book then continues with capsid modifications and viral-like particles as promising alternatives to classical adenovirus vectors, and the study of adenovirus in host interactions in vitro at the cellular level as well as in vivo in animal models. Finally, the volume concludes with an extensive update of the most efficient protocols to generate, amplify, and/or purify, at small and large scale, standard human Ad5 as well as non-human, chimeric, and helper-dependent adenovirus vectors. Written in the greatly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Comprehensive and cutting-edge, Adenovirus Methods and Protocols, Third Edition serves as an ideal guide for scientists continuing to research this highly valuable viral tool.
Biophysical Methods to Monitor Structural Aspects of the Adenovirus Infectious Cycle -- Proteome Analysis of Adenovirus Using Mass Spectrometry -- Capsid Modification Strategies for Detargeting Adenoviral Vectors -- Use of Dodecahedron “VLPs” as an Alternative to the Whole Adenovirus -- Study of Adenovirus and CAR Axonal Transport in Primary Neurons -- The Use of Chromatin Immunoprecipitation (ChIP) to Study the Binding of Viral Proteins to the Adenovirus Genome In Vivo -- DNA Microarray to Analyze Adenovirus-Host Interactions -- Determination of the Transforming Activities of Adenovirus Oncogenes -- Oncolytic Adenovirus Characterization: Activity and Immune Responses -- The Analysis of Innate Immune Response to Adenovirus Using Antibody Arrays -- Engineering Adenovirus Genome by Bacterial Artificial Chromosome (BAC) Technology -- Construction, Production, and Purification of Recombinant Adenovirus Vectors -- Scalable Production of Adenovirus Vectors -- Canine Adenovirus Downstream Processing Protocol -- Production of High-Capacity Adenovirus Vectors -- Production of Chimeric Adenovirus.
Keywords: Microbiology; Virology; Laboratory medicine; Microbiology; Virology; Laboratory Medicine